Pengaruh Beban Kerja dan Kompensasi terhadap Kepuasan Kerja Karyawan di Ocean Beach Hotel - Oxta Afriyanti; Youmil Abrian (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
This study aims to investigate the impact of workload and compensation on employee job satisfaction within Ocean Beach Hotel Padang. The research employs a quantitative approach, specifically a causal associative design, utilizing survey methods. The study's focus group consists of the employees working at Ocean Beach Hotel Padang. The primary data collection methods comprise literature reviews and the distribution of questionnaires among the selected research participants. The findings of this research indicate that, contrary to expectations, workload does not exert a significant influence on employee job satisfaction at Ocean Beach Hotel Padang. However, it was found that compensation does have a positive and substantial impact on employee job satisfaction within the same hotel. Interestingly, the study also uncovers that both compensation and workload indirectly contribute to enhancing employee job satisfaction at Ocean Beach Hotel Padang.